A PROGRESSIVE INTERPRETATION OF Q.S AN-NISA: 34: A COMPREHENSIVE EXPLORATION OF FAMILY LEADERSHIP IN THE FIELD OF GENDER - Arifin, Ahmad Zainal; Bachrul Falah, Mohammad (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Modernism's understanding of family law construction often targets women's capabilities as much as the head of the family. But in normative terms, women's leadership is textually inconsistent with the provisions of Surah an-Nisa: 34. The textuality of the sentence is now criticized by the gender idea that women can be placed on an equal footing with men if they can. The initiation aims to interpret Q.S. an-Nisa: 34 with Gadamer's hermeneutic theory, to better understand comprehensively the contextuality of sentences in the demands of the times. This research is library research by studying literature related to research topics. Using Gadamer's interpretation, it can be seen that Q.S. an-Nisa: 34 contains fertilization of family leadership more flexibly. The leadership of the head of the family can be held not only by men but also by women. However, it should also be based on a qualified person, that is, someone who can cater to the family's financial needs and has good leadership skills.